EPEN-28. Oncogenic dependency of pediatric ependymomas on extracellular vesicle pathways. (3rd June 2022) - Maass, Kendra K; Roosen, Mieke M; Mueller, Torsten; Senfter, Daniel; Benzel, Julia; Wedig, Tatjana; Kalxsdorf, Mathias; Krijgsveld, Jeroen; Pfister, Stefan M; Pajtler, Kristian W
Abstract: INTRODUCTION: The majority of pediatric ependymoma (EPN) comprise either supratentorial EPN characterized by ZFTA-fusions (ST-EPN-ZFTA) or posterior fossa group A EPN (PF-EPN-A), for both of which only limited therapeutic options are available. Because pediatric EPNs have a relatively low mutational burden, identification and characterization of tumor-associated pathways and molecular processes are of critical importance to reveal potential therapeutic targets. Data from previous transcriptional studies and a cross-species in vivo screen implied aberrant vesicular pathways in ST-EPN-ZFTA, prompting further investigation of their putative role in EPN pathogenesis. METHODS: We investigated EPN group-specific differences in extracellular vesicle (EV) biogenesis pathways in human EPN transcriptome and proteome datasets. In addition, we characterized isolated EPN EVs by mass spectrometry. EPN-specific EV cargo was further investigated by immunofluorescence staining and western blotting. This enhanced understanding of EPN vesicular signaling allowed for a pre-selection of inhibitors targeting specific EV biogenesis pathways. In vitro proliferation and invasion assays as well as in vivo treatment studies were performed on EPN model systems. RESULTS: Integration of multi-omic data from both EPN tissues and EPN-EV-associated proteome led to the identification of ST-EPN-ZFTA-specific EV populations. We could spatially map specific EV markers to the perivascular niche that primarily harbors undifferentiated ST-EPN-ZFTA cell populations. Targeting EV biogenesis pathways by inhibiting factors of the lipid metabolism reduced the abundance of released EVs resulting in altered growth behavior and decreased invasion of tumor cells in vitro . I n vivo validation of EV release inhibitors in an orthotopic ST-EPN-ZFTA PDX model significantly reduced tumor growth and increased survival. OUTLOOK: In summary, we have leveraged ST-EPN-ZFTA-specific EV pathways as a potential therapeutic vulnerability. Further mechanistic investigations on EPN EV biogenesis, release, or uptake are expected to improve our understanding of the cross-talk between tumor cells and cells of the microenvironment and may lead to potential new therapeutic avenues.